Effectiveness of a Recovery Program for Chinese Psychiatric Inpatients - LAI, LAI (International Journal of Psychosocial Rehabilitation, 2016)
This study is a retrospective evaluation study for a 63 Chinese clients with schizophrenia, bipolar affective dis - order, depression and adjustment disorder in recovery program. This study is going to note genders’ specific response to the recovery program and to identify predictors for their length of hospital stay. All recruited sub - jects would participate in a three-week recovery program. A series of goal setting training, psycho-education and empowerment activities, and therapeutic group sharing were included. Clients’ level of hope, mental-well - being, and ability in recovery and illness management would be assessed by Chinese Hope Scale (CHS), Chinese Short Warwick-Edinburgh Mental Well-being Scale (CSWEMWBS) and Chinese Illness Management and Recovery Scale (CIMRS). Subjects showed improvement in generating routes to recovery goals, enhanced capacity in initiating and maintaining the actions to reach their recovery goals. Moreover, clients showed signi - ficant improvement noted in seeking social support. Genders showed their specific characteristics in their pat - tern of recovery.